Introduction of Kanta services in social welfare is the key for utilising information - Hujanen, Kaisa; Ailio, Erja; Laukkanen, Hanne (Finnish Journal of eHealth and eWelfare, 2024)
Information management in social welfare is on the verge of a new era when social welfare organisations start using the Client data archive for social welfare services (part of the Kanta services). The objective of the development is to make the client data available where it is needed at any given time. Social welfare clients can view their data through MyKanta and professionals have access to uniform and up-to-date client data. Client data is stored in a comparable format, in which case the data can also be used in service development, research and knowledge management. The Client Data Act requires that wellbeing services counties start using Kanta services in social welfare. Preparedness in the wellbeing services counties on the eve of the introduction of the Client data archive for social welfare services varies. Almost all counties have started using the Client data archive for social welfare services, but in no region does the information system yet meet all the requirements of the Client Data Act. With the formation of wellbeing services counties, they still have many client information systems in use and in some information systems the implementation schedules may be delayed. The Client Data Act has been proposed to be amended so that the statutory transition periods for introducing the Client data archive for social welfare services would be extended from 6 months to one year. Even longer extensions of the introducing period have been proposed during the consultation round of the Client Data Act. Delaying the periods for introducing the Client data archive for social welfare services would also delay the availability of effectiveness information. Knowledge management is of primary importance in the wellbeing service counties and according to the PM Orpo’s government program information on the effectiveness of healthcare and social welfare is vital. Any delays in introducing the Client data archive for social welfare services threaten to postpone both the availability of effectiveness information and other benefits of Kanta services.